Zero contrast technique in doubly committed subarterial ventricular septal defect closure in patient with body weight less than 10 kg: a case report - Radityo Prakoso; Rina Ariani; Aditya Agita Sembiring; Brian Mendel; Oktavia Lilyasari (Frontiers in Cardiovascular Medicine)
IntroductionThe complex anatomy of DCSA VSD, its proximity to valvular and conduction tissues, and concerns about radiation and contrast make transcatheter closure particularly challenging in pediatric patients. While zero-fluoroscopy closure was not achievable in this case, we successfully performed zero-contrast transcatheter closure in a baby weighing less than 10 kg. This report highlights the feasibility and early outcomes of this approach at our institution.Case illustrationAn 18-month-old, 9 kg boy with a history of feeding difficulties, failure to thrive, and breathlessness since 14 days of age underwent transcatheter closure of a doubly committed subarterial (DCSA) ventricular septal defect (VSD). Transthoracic echocardiography revealed a 4–5 mm left-to-right shunting VSD with preserved ventricular function. Initial attempts to cross the VSD under zero-fluoroscopy guidance using various catheters were unsuccessful, necessitating fluoroscopic assistance without contrast. A Konar-MF VSD occluder (7/5 mm) was successfully deployed retrogradely, achieving complete defect closure with no residual shunt or valve dysfunction. Post-procedure, the patient remained asymptomatic, with excellent device positioning and no complications noted at follow-up.ConclusionThis case demonstrates the feasibility of zero-contrast percutaneous DCSA-VSD closure in selected patients weighing less than 10 kg. Further studies are needed to validate its safety and long-term outcomes.